2002
DOI: 10.1016/s0925-4773(01)00614-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for coordinated interaction of cyclin D3 with p21 and cdk6 in directing the development of uterine stromal cell decidualization and polyploidy during implantation

Abstract: Uterine decidualization, characterized by stromal cell proliferation, and differentiation into specialized type of cells (decidual cells) with polyploidy, during implantation is critical to the pregnancy establishment in mice. The mechanisms by which the cell cycle events govern these processes are poorly understood. The cell cycle is tightly regulated at two particular checkpoints, G1-S and G2-M phases. Normal operation of these phases involves a complex interplay of cyclins, cyclin-dependent kinases (cdks) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
151
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(155 citation statements)
references
References 34 publications
4
151
0
Order By: Relevance
“…This extensive cell proliferation and polyploidy event occurs in a well-organized manner. It firstly takes place at the antimesometrial side around the embryo on day 6, which is defined as primary decidual zone (PDZ) and then extends to the stromal cells next to the PDZ forming a fully developed zone around the PDZ, termed the secondary decidual zone (SDZ) [27]. This living embryo induced decidualization can also be mimicked by the application of artificial stimuli to a receptive pseudopregnant uterus, or one that has been appropriately primed by ovarian steroids, though not totally identical [28].…”
Section: Uterine Physiological Role In Normal Reproductive Eventsmentioning
confidence: 99%
“…This extensive cell proliferation and polyploidy event occurs in a well-organized manner. It firstly takes place at the antimesometrial side around the embryo on day 6, which is defined as primary decidual zone (PDZ) and then extends to the stromal cells next to the PDZ forming a fully developed zone around the PDZ, termed the secondary decidual zone (SDZ) [27]. This living embryo induced decidualization can also be mimicked by the application of artificial stimuli to a receptive pseudopregnant uterus, or one that has been appropriately primed by ovarian steroids, though not totally identical [28].…”
Section: Uterine Physiological Role In Normal Reproductive Eventsmentioning
confidence: 99%
“…The development of decidua or deciduoma in rodents is associated with the formation of multinucleate and giant cells (Sachs & Shelesnyak 1955, Ansell et al 1974, Moulton 1979, Tan et al 2002. The polyploid decidual cells are terminally differentiated cells and are shown to be developed through a unique process requiring transition from the mitotic cell cycle to an endoreduplication cycle (endocycle), in which cells undergo a repeated round of DNA replication without successive cell division (cytokinesis).…”
Section: Aspects Of Cellular Proliferation and Differentiation In Assmentioning
confidence: 99%
“…An altered cell cycle regulation has been considered to be associated with the development of cellular polyploidy. In mice, the development of decidual cell polyploidy leads to the generation of large mono-or binucleated cells, consisting of DNA with four, eight, and even higher multiples of the haploid complement (Sachs & Shelesnyak 1955, Ansell et al 1974, Moulton 1979, Tan et al 2002. Previous studies have shown that the antimesometrial decidualizing stroma is comprised of two populations of cells: first one that divides fast before undergoing differentiation and the second one that undergoes differentiation without further division, thus leading to the development of cellular heterogeneity in the decidual bed (Moulton 1979, Tan et al 2002.…”
Section: Aspects Of Cellular Proliferation and Differentiation In Assmentioning
confidence: 99%
See 2 more Smart Citations